2017
DOI: 10.3390/nu9070787
|View full text |Cite
|
Sign up to set email alerts
|

Iron Bioavailability Studies of the First Generation of Iron-Biofortified Beans Released in Rwanda

Abstract: This paper represents a series of in vitro iron (Fe) bioavailability experiments, Fe content analysis and polyphenolic profile of the first generation of Fe biofortified beans (Phaseolus vulgaris) selected for human trials in Rwanda and released to farmers of that region. The objective of the present study was to demonstrate how the Caco-2 cell bioassay for Fe bioavailability can be utilized to assess the nutritional quality of Fe in such varieties and how they may interact with diets and meal plans of experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 23 publications
(46 reference statements)
2
36
1
Order By: Relevance
“…Studies conducted to date on iron bioavailability from high-Fe biofortified beans using Caco-2 cell models are congruent with findings from poultry models 12 , 57 , which in turn are consistent with human feeding trials which have shown positive nutritional impacts from consumption of high-Fe biofortified beans 9 , 26 , 58 60 . However, antinutritional compounds in staple crop plants can negatively affect the uptake (bioavailability) of nutritional compounds (e.g.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Studies conducted to date on iron bioavailability from high-Fe biofortified beans using Caco-2 cell models are congruent with findings from poultry models 12 , 57 , which in turn are consistent with human feeding trials which have shown positive nutritional impacts from consumption of high-Fe biofortified beans 9 , 26 , 58 60 . However, antinutritional compounds in staple crop plants can negatively affect the uptake (bioavailability) of nutritional compounds (e.g.…”
Section: Discussionsupporting
confidence: 79%
“…The consideration of anti-nutritionals in biofortification breeding programs is important to ensure that efforts to increase the levels of micronutrients (e.g. iron) in crops are not compromised by inadvertent increases in levels of anti-nutritionals (such as phytic acid and/or polyphenols) that could arise from breeding efforts 9 , 11 , 13 , 15 , 16 or from environmental stresses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fructose 1,6-biphosphate, present at high levels in cabbage, has been shown to increase iron uptake in Caco-2 cells [37]. Potentially, incorporating microgreen vegetables in their dried forms into various recipes could make approximately 50% contribution per 100 g portion to the recommended daily iron intake in the diet [38]. For example, the reference nutrient intake (RNI) for iron in the UK is 14.8 mg per day for adult women.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted to date on the iron bioaccessibility and bioavailability from (iron biofortified) beans have been using Caco-2 cell models, in vitro digestion models [15][16][17][18][19][20][21], poultry studies [16,[20][21][22][23][24], and human feeding trials [25][26][27][28]. These studies show the influence of specific polyphenols on iron bio-accessibility and bioavailability depending on the type of bean.…”
Section: Introductionmentioning
confidence: 99%